(untitled) (Al-Asalmiya Nursing: Jurnal Ilmu Keperawatan (Journal of Nursing Sciences), 2023)
Face-to-face learning (PTM) during the transition period of the COVID-19 pandemic is the right time for parents to prepare their children to avoid preventing and transmitting the COVID-19 virus in the school environment. Parents must understand and know the importance of obeying health protocols and cultivating a Clean and Healthy Lifestyle (PHBS) in the context of preventing and controlling COVID-19 during the transition period of the COVID-19 pandemic. This study aims to identify a description of the knowledge and attitudes of parents in preparing face-to-face learning for school-age children during the transition period of the COVID-19 pandemic at SD Negeri 37 Pekanbaru City. This research is a quantitative research with a descriptive design. The population in this study were 107 grade 1 parents at SD Negeri 37 Pekanbaru City, with the sampling technique used was proportional random sampling. The analysis used in this study is univariate. Based on the characteristics of the age of the respondents in the age range of 18-40 years, the gender of the respondents is female, the average with the last education is high school, the average occupation of the parents is Housewives (IRT). Based on the level of knowledge, it was obtained that 56 respondents (52.3%) had sufficient knowledge, 35 respondents (32.7%) had good knowledge and 16 respondents (15.0%) had less knowledge. Based on the attitude obtained negative attitude as many as 62 respondents (57.9%) and have a positive attitude as many as 45 respondents (42.1%). Suggestions for respondents are expected to increase knowledge and attitudes towards the prevention of the COVID-19 virus in order to prepare children for face-to-face learning during the transition period of the COVD-19 pandemic and to prevent transmission of the COVID-19 virus in the school environment.